Nabokov's Art of Memory and European Modernism. - Foster, John Burt, Jr (Princeton University Press, 2001)
Despite Vladimir Nabokov's hostility toward literary labels, he clearly recognized his own place in cultural history. In a fresh approach stressing Nabokov's European context, John Foster shows how this writer's art of memory intersects with early twentieth-century modernism. Tracing his interests in temporal perspective and the mnemonic image, in intertextual "reminiscences," and in individuality amid cultural multiplicity, the book begins with such early Russian novels as Mary, then treats his emerging art of memory from Laughter in the Dark to The Gift. After discussing the author's cultura.